2005
DOI: 10.1111/j.1463-1318.2005.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled flaps in the treatment of nonhealing perineal wounds

Abstract: A gracilis transposition is a relatively simple operation with minimal morbidity useful for superficial sinuses not requiring a muscle bulk. A rectus abdominis flap is a more complex specialized procedure with better results especially in dealing with larger cavities but it may compromise future stoma sites. Omentoplasty has excellent results, but is only available in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…7,12,13 The current study is the largest study to date reporting exclusively on the outcome of gracilis muscle transposition for complicated perineal wounds in Crohn's disease. This study showed the healing rate without recurrence in nearly two-thirds of the patients after 10 months, and this was maintained in all but 1 of the patients who were available for medium-to long-term follow-up.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…7,12,13 The current study is the largest study to date reporting exclusively on the outcome of gracilis muscle transposition for complicated perineal wounds in Crohn's disease. This study showed the healing rate without recurrence in nearly two-thirds of the patients after 10 months, and this was maintained in all but 1 of the patients who were available for medium-to long-term follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…In cases with a very large defect and when extra bulking is needed, bilateral transposition or a supplementary omental patch may increase the chance of healing. 12 In this study, the assessment of fistula healing was based on clinical examination. Although the extent of active sepsis and the complexities of the fistula tract were determined by magnetic resonance imaging prior to the operation, improvement was not monitored by any imaging, and this needs to be considered in any prospective study to evaluate ''deep'' healing of the underlying tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The gracilis muscle flap does have the advantage of being an expendable muscle in the inner thigh that can be harvested with limited incisions and minimal donor site morbidity and transposed on a predictable vascular pedicle with adequate length to reach the perineum. This reconstructive option is less invasive and has less donor site morbidity when compared with the use of the other described options such as the rectus abdominus or omentum, considering the significant extra-abdominal and intraabdominal scar burden on patients with a history of multiple abdominal surgeries [3,15]. Bilateral gracilis muscle flaps can be used for large perineal defects with similar low donor site morbidity.…”
Section: E39mentioning
confidence: 98%
“…There are several operative options; however, they have for the most part have been studied only in adult populations. In the adult literature, the most common techniques include injection with biologic glue, rectal or vaginal advancement flaps, and muscle flap interposition [1][2][3][4]. Often 2 or more procedures are required before a durable result is achieved [5].…”
mentioning
confidence: 99%
“…2,3 With regard to the management of this complication, most studies have reported the outcome in a relatively small number of cases, without longterm follow-up. [4][5][6][7][8] This study was designed to determine the incidence of PPS after pouch excision in inflammatory bowel diseases (IBD), to identify the risk factors for this complication, and to determine the clinical course and outcome of management in patients with PPS.…”
mentioning
confidence: 99%